Educators' Perspectives of the Processes of Communication between Preschool and Primary School Sectors - Brazel, Danielle (My University, 2018)
The interest in transition has grown over the past decade, in both national and international literature (CECDE, 2006a; Hopps, 2014; Hopps & Dockett, 2011; O' Kane, 2016; O'Kane & Hayes, 2006, 2010; Ring et al., 2016). The quality of communication between the professionals who work in either sector can have an effect on the success of a child's transition (Hopps, 2014; Hopps & Dockett, 2011; O' Kane, 2016; Ring et al., 2016). Although there is a wealth of research on the importance of communication and transferring documentation there is less formal guidance on what information should be transferred and how (ETC Research Group, 2011 cited by O'Kane, 2016).This research aims to answer the question: What are educators' perceptions of the processes of communication between the preschool and primary school sectors at the time of transition, including facilitators, barriers and strategies to improve communication? The sample was six primary school teachers and six preschool teachers, in Ireland. A qualitative design, using semi-structured interviews, was chosen as the research method. It was viewed as the most appropriate design for the data desired (Merriam, 2009) as the aim was to collect individual perspectives on the topic. The data analysis showed general cohesion on the importance of transition and professional communication while showing some difference in opinion amongst the participants of the barriers, facilitators and strategies for communication. While the findings show that there are communication strategies that can be adopted with some effort and time devoted to them, many things would have to change at policy level to encourage a coordinated system of communication.
Master in Education Studies (Early Childhood Education)
Keywords: Research Subject Categories; Communication; Preschool; Primary school; Transition